Viscoelastic and dielectric behavior of poly(1-butene)/multiwalled carbon nanotube nanocomposites - Wanjale, Santosh D.; Jog, Jyoti Prakash (Journal of Macromolecular Science Part B-Physics, 2006)
Linear viscoelastic properties and dielectric behavior of poly(1-butene)/multiwalled carbon nanotube (MWCNT) nanocomposites were investigated. Dynamic mechanical analysis showed significant increase in storage modulus in the rubbery regime. The tan delta peak temperature remained constant; however, the peak intensity was lowered for the nanocomposites. In melt rheological studies the nanocomposites showed a shift in crossover frequency to the lower side, suggesting delayed relaxation of the molecular chains in the presence of MWCNT and this shift was found to depend on the content of MWCNT. The dielectric constant increased from 2.2 to 70 for the nanocomposite with 7 wt. % MWCNT. The electrical conductivity increased significantly, from 10(-15) to 10(-3) S/cm. The results of rheology and dielectric studies indicate that a percolation network is formed that is responsible for the observed changes.
Keywords: Dielectric; MWCNT; poly(1-butene); viscoelastic

Mechanics of soft polymeric materials using a fractal viscoelastic model - Pramanik, R.; Soni, F.; Shanmuganathan, K.; Arockiarajan, A. (Mechanics of Time-Dependent Materials, 2022)
Soft materials are known for their plethora of biomedical applications, intricate structure-property correlation and nonlinear mechanical response. Multiple length-time scale phenomena and hierarchical structure results in their nonlinearity. Phenomenological and continuum mechanical models have been developed to predict their mechanics, which have mostly been very material-specific with inability to predict the mechanics of different types of soft materials simultaneously. This shortcoming has been addressed in the present work, wherein a generic nonlinear viscoelastic model has been proposed to predict the mechanical response of hydrogels, sponges, and xerogels. A fractal derivative viscoelastic model is proposed considering a fractal Maxwell model in parallel with a nonlinear spring. In particular, this model is chosen to qualitatively mimic the material nonlinearity inherent in soft materials. The fractal dashpot in combination with the nonlinear spring accounts for the power law time-dependent rheology of generic soft materials. These two different aspects in the form of nonlinear stiffness and non-Newtonian rheology account for mechanics of most soft materials. The present model is shown to fit well the existing literature results for mechanical response of a multitude of soft material classes with different test conditions and loading rates, which is one of the salient features of the model, apart from its simplistic mathematical framework. Further, a parametric study is reported on the mechanics of nanocellulose loaded poly(vinyl alcohol) xerogel. The model predictions are observed to be in conjunction with the experimental observations.
Keywords: Mechanics; Nonlinear; Polymeric composites; Soft materials; viscoelastic

Viscoelastic liquid from regenerated silk fibroin in the silk i conformation: a writeable and shapeable material - Kumar, Raj; Joseph, Emmanuel; Chaudhari, Atul; Nisal, Anuya; Sharma, Kamendra P. (ACS Applied Polymer Materials, 2022)
Regenerated silk fibroin (RSF) has acquired enormous attention because of its exceptional toughness, strength, and biocompatible nature. These properties make RSF a potential candidate for the fabrication of different types of materials. However, processing even a dilute aqueous solution of RSF leads to a conformational transformation from a random coil/helix-rich (silk I) to a beta-sheetrich (silk II) state. As a consequence, RSF tends to form aggregates and loses its toughness. Working in a direction to address this problem, an aqueous solution of regenerated silk fibroin has been modified with a dual layer of polyethylenimine (PEI) and a PEG-based polymer surfactant (PS). Upon freeze-drying, the RSF-polymer complex forms a solvent-free RSF bioconjugate system and exhibits a soft solid to liquid melting transition at similar to 45 degrees C. The sequential modification with PEI and PS preserves the native-like random coil conformation of RSF up to at least 8 months of storage by not allowing interchain interactions that can lead to aggregation. Rheological and small-angle X-ray scattering measurements show that the solvent-free system is viscoelastic and exhibits a higher order microstructure mediated by the packing of the PS chains, respectively. Temperature-dependent soft solid-liquid-like dual behavior offers applications in injection-based writing, compression molding, and shaping RSF bioconjugates into various types of geometries. Furthermore, the mechanical properties of the RSF bioconjugate system can be modulated by crosslinking with glutaraldehyde vapor at 50 degrees C.
Keywords: RSF liquid; RSF soft solid; silk I conformation; silk liquid; viscoelastic